Simulation of the use of porous pavement and infiltration trench in public spaces supporting mobility - Montagna, Talita; Vieira, Rafaela; Kaufmann, Vander; Pinheiro, Adilson; Paulo Michel, Gean (Sustainability in Debate, 2021)
The use of sustainable techniques to the basic infrastructure of a city is a way of win back public spaces. This study evaluates the impacts of public spaces supporting mobility. We give focus to areas constructed with porous pavement and integrated with infiltration trenches and hydrological processes. The hydrological simulation was performed with a SWAT model. The hydrographic basin has 54.05 km² and the area of excess flows' control is 0.66 km². The peak flow damping was 1.84%, and the surface runoff represented 2.82% of the water depth over the simulated period. We observed a maximum reduction of 7.9% in the height of the water layer for isolated events. We found positive results in the dampening of the peak flow in the basin exhaust and water flow reduction at the superficial runoff.